Trends in use of genotypic resistance testing and frequency of major drug resistance among antiretroviral-naive persons in the HIV Outpatient Study, 1999–2011. (15th May 2015) - Buchacz, Kate; Young, Benjamin; Palella, Frank J.; Armon, Carl; Brooks, John T.; ,; Buchacz, Kate; Brooks, John T.; Durham, Marcus D.; Hays, Harlen; Wood, Kathleen C.; Hankerson, Darlene; et al.
Abstract: Background: Monitoring antiretroviral drug resistance can inform treatment recommendations; however, there are few such data from US patients before they initiate ART. Methods: We analysed data from HIV Outpatient Study (HOPS) participants from nine US HIV clinics who were diagnosed with HIV infection during 1999–2011. Using the IAS-USA December 2010 guidelines, we assessed the frequency of major drug resistance mutations (mDRMs) related to antiretroviral agents in viral isolates from patients who underwent commercial genotypic testing (GT) for resistance before initiating ART. We employed general linear regression models to assess factors associated with having undergone GT, and then factors associated with having mDRM. Results: Among 1531 eligible patients, 758 (49.5%) underwent GT before first ART, increasing from 15.5% in 1999–2002 to 75.9% in 2009–11 ( P < 0.001). GT was carried out a median of 1.2 months after the diagnosis of HIV. In adjusted regression analyses, patients with pre-ART CD4+ T lymphocyte counts ≥200 cells/mm 3 or with HIV RNA levels >5.0 log10 copies/mL and those with a first HOPS visit in 2006 or later were significantly ( P < 0.05) more likely to have undergone GT. Of the 758 patients, 114 (15.0%) had mDRMs; mutations relating to NRTIs, NNRTIs and PIs were present in 8.0%, 7.1% and 2.6%, respectively. There was no temporal change in the frequency of mDRM, and mDRMs were associated with an HIV RNA level <4.0 log10 copies/mL. Conclusions: During 1999–2011, GT use among antiretroviral-naive patients became more common, but a quarter of patients in recent years remained untested. The frequency of mDRMs remained stable over time at about 15%.